Condition of cognitive function on the first week after an operation using general anesthesia - Dubivska Світлана; Hryhorov Юрій (Psychosomatic Medicine and General Practice, 2019)
To achieve this goal, we conducted a study of the cognitive sphere in patients of different age groups: young age, middle age, elderly people with acute surgical pathology before surgery and on the 1st and 7th days after surgery in comparison with preoperative data. According to the results of the MMSE test, in the middle-aged patients the dynamics of the deterioration of the cognitive function were observed to a lesser degree than in the young patients, which is probably related to the age-related features of the plasticity of the cognitive function. In patients of middle age, according to the results of the FAB scale, at this period of the study was at the same level as those in young patients, which may be related to the age-related features of the plasticity of the cognitive function. According to the test drawing hours, there was no significant difference in the speed of recovery, it was gradual, but no complete restoration was observed. According to the memory test of 10 words and the Schulte test parameters, the recovery was gradual, with a complete restoration of the indicator to the level before the operation.